2021
DOI: 10.1002/hyp.14286
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impact of no‐till on sediment yield in southern Brazil at the hillslope and catchment scales

Abstract: No-till (NT) is a soil management system designed to protect soil resources from water erosion and provide numerous benefits compared to conventional tillage through the increase of organic matter inputs into the soil. However, NT in isolation is not sufficient to control erosion processes caused by an excessive production of surface runoff. This study evaluated soil losses on agricultural hillslopes under no-till characterized by contrasted water, soil, and crop management conditions. To this end, water and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…The research presented in this study concludes that both stone dike terraces and earth‐banked terraces effectively reduce soil erosion on slopes under ordinary rainfall conditions. This conclusion is consistent with previous research findings (Al‐Seekh & Mohammad, 2009; Gathagu et al, 2018; Hammad et al, 2004; Li et al, 2012; Londero et al, 2021; Pijl et al, 2020; Subhatu et al, 2018). However, when it comes to their impact on runoff generation, these conclusions diverge significantly.…”
Section: Discussionsupporting
confidence: 93%
“…The research presented in this study concludes that both stone dike terraces and earth‐banked terraces effectively reduce soil erosion on slopes under ordinary rainfall conditions. This conclusion is consistent with previous research findings (Al‐Seekh & Mohammad, 2009; Gathagu et al, 2018; Hammad et al, 2004; Li et al, 2012; Londero et al, 2021; Pijl et al, 2020; Subhatu et al, 2018). However, when it comes to their impact on runoff generation, these conclusions diverge significantly.…”
Section: Discussionsupporting
confidence: 93%
“…From an equivalent of 360 plot yr across five Brazilian states, Fonseca et al (2021) retrieved soil losses ranging from a minimum of 8.9 to a maximum of 205.7 t ha −1 yr −1 . They also showed that soil losses under conservation agriculture experience erosion rates that are 70% lower than those measured under conventional agriculture, underlining the importance of permanent vegetation cover to reduce tillage and limit runoff and thus soil erosion (see also Anache et al, 2017Anache et al, , 2019Castro et al, 1999;Londero et al, 2021).…”
Section: Brief Review Of Natural Denudation and Human-induced Erosion...mentioning
confidence: 99%
“…1). Detailed information on the site's characteristics and direct measurements' obtention can be found in Londero et al (2021aLondero et al ( , 2021b and Schneider (2021). Further information is presented in Tables 1 and 2 in the supplementary material.…”
Section: Soil Erosion Modelingmentioning
confidence: 99%